Consular Access and the Protection of Nigerian Illegal Residents and Detainees in Saudi Arabia - Ibrahim Danguguwa, Kabiru; Hotoro, Bello Adamu; Ogbaji, Ogoh Augustine; Ibrahim, Abba Bala (Golden Ratio of Social Science and Education, 2025)
This study examines the extent of consular access and protection available to Nigerian nationals through the Nigerian Consulate in Saudi Arabia. Nigerians have long been central to the diplomatic relationship between Nigeria and Saudi Arabia. Over the years, various efforts have been made to safeguard the rights and welfare of Nigerians residing in the Kingdom. Since 1982, Nigeria has maintained a consulate in Jeddah, established by the provisions of the Vienna Convention on Consular Relations (1963). This study is based on data collected through interviews with 13 purposively selected participants, including staff of the Nigerian Consulate in Jeddah, irregular (undocumented) residents, and detained Nigerian nationals. The findings reveal that over 80% of Nigerians residing in Saudi Arabia do so without legal documentation, with a smaller portion comprising arrested and/or imprisoned individuals. The study shows that irregular residents face significant challenges in accessing consular services, primarily due to fear of deportation, which discourages them from engaging with the consulate. On the other hand, most arrested individuals were legal residents, typically accused of offenses related to illicit substance trafficking or other violations of Saudi law. While some were found guilty, many convicted Nigerians reported a lack of adequate support and follow-up from consular officials during their imprisonment. In conclusion, both irregular residents and arrested Nigerian nationals are exposed to heightened vulnerability in the absence of adequate and accessible consular protection in the Kingdom of Saudi Arabia.